Effective Management of Private Schools in Nigeria: Necessity for Governments’ Intervention - John Oluyemi Egbebi; Olayinka Tijani Wakili (RIRAI Publisher, 2020)
Private schools and owners invest a lot of worthwhile input in the provision of functional educational service delivery thus paving way for further access, equity and fair play to every intending learner as complement to the effort of government, the public school providers in Nigeria. This development actually met the world declaration of the expectation from all nations of the world to provide mass, quality and free education to all citizens. By and large, education service delivery as a social service requires huge sum of money in its operations across all levels of educational institutions – basic, post basic and tertiary. The paper examined effective management of private schools in Nigeria and the necessity for governments’ intervention. In a nutshell, the paper espoused: the world demand on provision of quality education; available sources of funding for private school ownership; challenges of private school ownership and management; justification for the establishment of private schools to support government established institutions; comparism of funding and management pattern of private schools in Nigeria and diaspora; and core constraints of private schools. The paper concludes and recommends that, respective governments, their agencies and parastatals should participate actively in rendering adequate support regarding award of grant-in-aid to owners of private schools; and that cost of registration and set up cost on infrastructural facilities for private schools - low, medium and high scales should be cut down by FME or SMoEs , ZIE, LIE, UBEC, TRCN, and similar institutions thus, affordable to create more access to learners with standards.